Study the Effectiveness of Plants Extract Against Urinary Tract Infections - Al-Zubaidi, Arjwan M.; Hassan, Zahraa M.; AbdAlkhaliq, Ghufran Q. (PROSPECTIVE RESEARCHES, 2025)
Urinary tract infections (UTIs) are among the most common bacterial infections worldwide, primarily caused by pathogens such as Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis. The increasing prevalence of antibiotic-resistant strains has intensified the need for alternative therapeutic approaches. Medicinal plants, with their bioactive compounds, offer a promising solution due to their antimicrobial, anti-inflammatory, and immune-modulatory properties. This review highlights the potential of medicinal plants in managing bacterial UTIs, focusing on their phytochemical constituents such as flavonoids, tannins, alkaloids, and essential oils. Plants like Cranberry (Vaccinium macrocarpon), Bearberry (Arctostaphylos uva-ursi), Neem (Azadirachta indica), and Garlic (Allium sativum) exhibit significant antibacterial activity against UTI pathogens. Mechanisms of action include inhibition of bacterial adhesion, disruption of biofilm formation, and suppression of quorum sensing. Furthermore, plant-based remedies are a good supplement or substitute for traditional medicines due to their safety, effectiveness, and affordability as well as their capacity to lessen antibiotic resistance. To prove their therapeutic effectiveness, however, more clinical research and dosage and formulation uniformity are essential. In order to address the growing problem of bacterial UTIs, this study highlights the merging of contemporary scientific research with ethno pharmacological knowledge.